Housing Wealth Across Countries: The Role of Expectations, Institutions and Preferences - Julia Le Blanc; Jiri Slacalek; Matthew N. White (CESifo GmbH, 2025)
Homeownership rates and holdings of housing wealth differ immensely across countries. We specify and estimate a life cycle model with risky labor income and house prices in which households face a discrete–continuous choice between renting and owning a house, whose sale is subject to transaction costs. The model allows us to quantify three groups of explanatory factors for long-run, structural differences in the extensive and intensive margins of housing: the homeownership rate and the value of housing wealth of homeowners. First, in line with survey evidence, we allow for differences in expectations of house prices. Second, countries differ in the institutional set-up of the housing market: maximum loan–value ratio and costs of renting, maintaining, and selling a house. Third, we allow for differences in household preferences: the dispersion in discount factors, the share of housing expenditure, and the bequest motive. We estimate the model using micro data from five large economies and provide a decomposition to interpret what drives the cross-country differences in housing wealth. We find that all three groups of factors matter, although preferences less so. Differences in homeownership rates are strongly affected by (i) house price beliefs and (ii) the rental wedge, the difference between rents and maintenance costs, which reflects the quality of the rental market. Differences in the value of housing wealth are substantially driven by housing maintenance costs.
Keywords: D15; D31; D84; E21; G11; G51; 330; housing; homeownership; house price expectations; housing market institutions; cross-country comparisons